The English Clergy and the Hundred Years War - McHardy, Alison K. (Studies in church history, 1983)
The Contribution made by the Church to the English war effort during the Hundred Years War was immense. It is the purpose of this paper to describe the forms which this contribution took, and then to offer some reflections on it.The most important clerical contribution to the war was financial: the taxes voted by the clergy in their two convocations and collected by themselves for the benefit of the crown. These corresponded to the lay subsidies voted in parliament. Normally such taxes were tenths of clerical income as it had been assessed, about 1291, for the benefit of the papacy. No new assessment of clerical wealth was made in the fourteenth or fifteenth centuries, but during the decade 1371 to 1381 a series of experimental taxes was levied from clergy and laity alike. These experiments, culminating in the notorious poll tax of 1380-1 which provoked open rebellion, were not repeated. But in the fifteenth century successive governments tried to tap the wealth of the chantry and stipendiary chaplains through a series of taxes of the poll tax type. Unlike the fourteenth-century poll taxes these measures were imposed at infrequent intervals (in 1406, 1419, 1430, 1436, 1449), but, like them, were abandoned because they failed to bring in the hoped-for revenue.